2011
DOI: 10.1016/j.bbamcr.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 modulates actin dynamics: Inhibition of HSP90 leads to decreased cell motility and impairs invasion

Abstract: HSP90, a major molecular chaperone, plays an essential role in the maintenance of several signaling molecules. Inhibition of HSP90 by inhibitors such as 17-allylamino-demethoxy-geldanamycin (17AAG) is known to induce apoptosis in various cancer cells by decreasing the activation or expression of pro-survival molecules such as protein kinase B (Akt). While we did not observe either decrease in expression or activation of pro-survival signaling molecules in human breast cancer cells upon inhibiting HSP90 with 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 39 publications
5
41
0
Order By: Relevance
“…When HSP70 was inactivated using shRNA knockdown in cell lines from cervical and bladder cancer, invasion and migration was also suppressed, in the same way these phenotypes are affected by WASF3 knockdown. In other studies of breast cancer (17), treatment with 17-AAG led to decreased filopodia and lamellipodia formation, as well as actin bundles and actin polymerization. These changes were associated with decreased invasion, as we demonstrated for different cell lines in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When HSP70 was inactivated using shRNA knockdown in cell lines from cervical and bladder cancer, invasion and migration was also suppressed, in the same way these phenotypes are affected by WASF3 knockdown. In other studies of breast cancer (17), treatment with 17-AAG led to decreased filopodia and lamellipodia formation, as well as actin bundles and actin polymerization. These changes were associated with decreased invasion, as we demonstrated for different cell lines in this study.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 has emerged as a promising target for the treatment of cancer and inhibition of its function by the 17-AAG drug leads to decreased cancer cell motility and invasion (15)(16)(17). We have recently demonstrated that WASF3 is important in controlling cell motility and invasion in breast and prostate cancer cells (2,3,5).…”
Section: Wasf3mentioning
confidence: 99%
“…It dynamically distributes in almost every cellular compartment: the cytoplasmic HSP90, which is the dominant form in the cell and is comprised of a and b isoforms; the endoplasmic reticulum-localized HSP90 protein glucose-regulated protein 94; and the mitochondrial HSP90, which includes the TNF receptorassociated protein (TRAP) family member TRAP1 (14). Recently, it was shown that HSP90 regulates the migration of endothelial cells or tumor cells by influencing cell membrane polarization, which is mainly mediated by the PI3K-AKT pathway (1,(15)(16)(17). Given the similarity between tumor cells and leukocytes with respect to their amoeboid migration (18), HSP90 could also be involved in interstitial leukocyte migration; thus, targeting HSP90 could ameliorate inflammation-associated diseases.…”
mentioning
confidence: 99%
“…Although calpain (29,30) and HSP90 (31) have been independently implicated in promoting cell migration and invasion, cooperative effects have not been described. 17AAG alone suppressed MBA-MB-231 cell migration by 20% (P ϭ 4.47 ϫ 10 Ϫ4 ) and 17% (P ϭ 4.44 ϫ 10 Ϫ4 ) at 10 and 25 M, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell migration and metastasis are two essential processes of the metastatic cascade. HSP90 (31) and calpain (29,30) have previously been shown to positively regulate these processes. Inhibition of HSP90 or calpain knockdown was associated with decreased in vitro migration and invasion ( Fig.…”
Section: Discussionmentioning
confidence: 99%